Church of St. John in Stivanje polje on Dugi otok (In situ, 2024)
The paper describes previous investigations in the church of St. John and its surroundings in Stivanje polje within the Telašćica Nature Park with focus on the 2023 campaign. Along with several medieval graves, one of the rooms of the Roman farming complex on which the church was built was fully investigated.
Keywords: Sv. Ivan; Stivanje polje; Telašćica; Dugi otok; church; medieval necropolis; Roman farming complex